The Role of Arts and Culture in Increasing Social Awareness: Peran Seni dan Kebudayaan dalam Meningkatkan Kesadaran Sosial - Indah Rarasati; Desy Safitri; Sujarwo (Jurnal Intelek Dan Cendikiawan Nusantara, 2024)
This journal explores the role of art and culture in enhancing social awareness. Through in-depth analysis, the study highlights how artistic expressions and local wisdom contribute to the community's understanding of social issues. Findings indicate that art and culture have significant potential to shape perceptions and strengthen social cohesion.